Agile methods : 10th Brazilian Workshop, WBMA 2019, Belo Horizonte, Brazil, September 11, 2019, Revised selected papers /: 10th Brazilian Workshop, WBMA 2019, Belo Horizonte, Brazil, September 11, 2019, Revised selected papers. (©2019) - Unknown
No abstract available